Teaching the Silk Road : a guide for college teachers - Wendelken, Rebecca Woodward; Moore, Jacqueline M., 1965- (SUNY series in Asian studies development., 2010)
The romance of the Silk Road journey, with its exotic locales and luxury goods, still excites the popular imagination. But study of the trade routes between China and central Asia that flourished from about 200 BCE to the 1500Æs can also greatly enhance contemporary higher education curricula. Indeed, with people, plants, animals, ideas, and beliefs traversing it, the Silk Road is both a metaphor of globalization and an early example of it.